PENGARUH PARITAS DAYA BELI DAN PARITAS SUKU BUNGA, TERHADAP NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA SERIKAT - Adhawiyah, Robiatul; Prajawati, Maretha Ika; Firdian, Rieza (IQTISHODUNA, 2018)
The exchange rate will react against change of inflation and interest rate, at least there are three theories that explain the relationship between inflation, interest rate, and exchange rate, namely purchasing power parity, interest rate parity, and international fisher effect. The purpose of this study was to determine the influence of purchasing power parity, interest rate parity, and international fisher effect on the Rupiah exchange rate against US Dollar. The populations in this research included inflation time series data, nominal interest rate, real interest rate, and Rupiah exchange rate. The data used in is secondary data form the inflation report, nominal interest rate, real interest rate, and Rupiah exchange rate quarterly. The independent variable used purchasing power parity, interest rate parity, and international fisher effect,the dependent variable used the Rupiah exchange rate against US Dollar. The result of this study indicated that the purchasing power parity, interest rate parity simultaneously had a significant influence on the exchange rate of Rupiah/US Dollar.